2019
DOI: 10.1111/febs.14781
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the unique polylactate‐degrading mechanism of Thermobifida alba cutinase

Abstract: Cutinases are enzymes known to degrade polyester‐type plastics. Est119, a plastic‐degrading type of cutinase from Thermobifida alba AHK119 (herein called Ta_cut), shows a broad substrate specificity toward polyesters, and can degrade substrates including polylactic acid (PLA). However, the PLA‐degrading mechanism of cutinases is still poorly understood. Here, we report the structure complexes of cutinase with ethyl lactate (EL), the constitutional unit. From this complex structure, the electron density maps cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…Hydrolysis of synthetic polymers such as PET (Dimarogona et al, 2015), polycaprolactone (Adıgüzel and Tunçer, 2017), polystyrene (PS) (Ho et al, 2018), polyethylene furanoate (Weinberger et al, 2017), and polybutylene succinate (Hu et al, 2016) have also been reported using cutinase. Cutinase-mediated hydrolysis of polylactic acid is also demonstrated by several authors (Masaki et al, 2005;Kitadokoro et al, 2019).…”
Section: Enzymes Used For Pet Hydrolysismentioning
confidence: 67%
“…Hydrolysis of synthetic polymers such as PET (Dimarogona et al, 2015), polycaprolactone (Adıgüzel and Tunçer, 2017), polystyrene (PS) (Ho et al, 2018), polyethylene furanoate (Weinberger et al, 2017), and polybutylene succinate (Hu et al, 2016) have also been reported using cutinase. Cutinase-mediated hydrolysis of polylactic acid is also demonstrated by several authors (Masaki et al, 2005;Kitadokoro et al, 2019).…”
Section: Enzymes Used For Pet Hydrolysismentioning
confidence: 67%
“…The mechanism of PLA degradation by a cutinase from T. alba has been recently reported [40] . The cutinase ( T.alba cutinase Est119) has a sequence similar to AML (61% sequence identity, 73% sequence similarity).…”
Section: Resultsmentioning
confidence: 99%
“…It was clear from this alignment that there was significant overlap in the key catalytic residues for these enzymes. The structural differences were further explored by superimposing the 3D model of AML on the crystal structure of Est119 crystallised with bound PLA analogues ethyl acetate (EL) and lactic acid (LAC; PDB: 6AID) [40] . Both structures were aligned using PyMOL to compare the reported catalytic and substrate recognition sites for PLA degradation (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Residue X acid+2 , one of the conserved structural elements that is involved in the coordination of the imidazole ring of the catalytic histidine, is usually a hydrophobic or an aromatic residue located at the entrance of the active site cleft, mostly reviewed for its role in ligand binding [51][52][53][54][55][56] or the release of products of catalysis [51,57]. Consequently, the site-directed mutagenesis of residue X acid+2 in different ABH enzymes has led to various results, which are consistent with its role in ligand binding, including the compromising [52,54,55,58,59] or the enhancement [52] of catalytic activity, the alteration of transport tunnels [57,60], the modification of substrate specificity [53,55,56] and the inversion of enantioselectivity [52]. For the remaining residues that coordinate the imidazole ring of the catalytic histidine, including residue X acid+3 , we have only found a few mutational studies that have resulted in reduced activity [58,61,62], with a single study highlighting the residue's role in the stability of the enzyme and the catalytic activity rather than in ligand binding [58].…”
Section: The Conserved Structural Elements That Line the Catalytic Stmentioning
confidence: 99%